2020
DOI: 10.3390/rs12203301
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Data Balancing Method for Classification of Imbalanced Training Data within Google Earth Engine: Case Studies from Mountainous Regions

Abstract: Distribution of Land Cover (LC) classes is mostly imbalanced with some majority LC classes dominating against minority classes in mountainous areas. Although standard Machine Learning (ML) classifiers can achieve high accuracies for majority classes, they largely fail to provide reasonable accuracies for minority classes. This is mainly due to the class imbalance problem. In this study, a hybrid data balancing method, called the Partial Random Over-Sampling and Random Under-Sampling (PROSRUS), was proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…To date, three approaches have been proposed to address the class imbalance problem: (1) applying specific classification methods by focusing on the learning of minority classes, (2) assigning higher weights on minority classes by adjusting classifiers, and (3) rebalancing training datasets (e.g., oversampling and under-sampling techniques). A hybrid data-balancing method, called the Partial Random Over-Sampling and Random Under-Sampling (PROSRUS), was proposed in [96] to resolve the class imbalance issue. The class imbalance problem reduces classification accuracy for infrequent and rare LC classes.…”
Section: Land Cover Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three approaches have been proposed to address the class imbalance problem: (1) applying specific classification methods by focusing on the learning of minority classes, (2) assigning higher weights on minority classes by adjusting classifiers, and (3) rebalancing training datasets (e.g., oversampling and under-sampling techniques). A hybrid data-balancing method, called the Partial Random Over-Sampling and Random Under-Sampling (PROSRUS), was proposed in [96] to resolve the class imbalance issue. The class imbalance problem reduces classification accuracy for infrequent and rare LC classes.…”
Section: Land Cover Classificationmentioning
confidence: 99%
“…The authors in [96] proposed a hybrid data balancing method, called the Partial Random Over-Sampling and Random Under-Sampling (PROSRUS), to resolve the class imbalance issue. PROSRUS used a partial balancing approach with hundreds of fractions for majority and minority classes to balance datasets.…”
Section: Appendix a The Accompanying Interactive Web App Tool For The...mentioning
confidence: 99%
“…As can be seen in Table 4 and Table 5, both minority and majority classes show acceptable UA and PA values while it has been reported that standard ML classifiers (i.e., RF) often fail to achieve reasonable accuracies for minority classes [62,63]. The reason can be that the proposed classification scheme divides the study area into smaller sub-areas and substantially avoids the occurrence of the data imbalance issue.…”
Section: B Performance Of the Proposed Classification Schemementioning
confidence: 92%
“…However, the proposed methodologies have primarily examined specific landscapes, and their performances in different landscapes have not been investigated. For example, Naboureh et al [20] proposed a hybrid data balancing method for mountainous regions. In another study, Waldner et al [21] investigated the impact of different data balancing techniques for mapping crops.…”
Section: Introductionmentioning
confidence: 99%